Teachers’ awareness on the use of technology in teaching islamic education a study at Setiabudi secondary school, Gombak, Selangor - Siregar, Zainal Abidin; Nik Abdullah, Nik Md. Saiful Azizi; Arifin, Abdul Gafur; Muhammad Isa, Rabi'atul Athirah (2023)
This study aims to explore the awareness of Islamic education teachers on the use of technology in teaching Islamic education. Specifically, the objectives of this research are; to investigate the teachers’ perspective on the use of technology-based teaching methods in teaching of Islamic education and to explore the teachers’ usage of technology in teaching of Islamic education. This study is a qualitative case study using semi-structured interview to collect the intended data. Three Islamic education Teachers from Setiabudi School Gombak, Malaysia was selected through purposive sampling. The informants were selected based on their qualifications and teaching experiences, and the data were analysed using thematic analysis. The findings of the study revealed two major themes, namely the teachers’ perspectives on technology based-teaching and the use of technology in teaching Islamic Education. The first theme indicates that the technology-based teaching refers to the use of technology as the teaching aids to help teachers deliver the lessons and to ease and facilitate the students’ learning. The second theme revealed that the use of technology in teaching Islamic education should consider the appropriateness of the particular technology with the learning materials or teaching method. The study also shows that the Islamic education teachers need to have a strong belief on the use of technology, considering the availability of the students accessing the technology; and the school must support the current needs toward technology based-teaching.